VISI BARU: KEKUATAN IMAJINASI DAN KEBARUAN-KEBARUAN ESTETIK - Moh. Rusnoto Susanto (Faculty of Humanities, Jember University, 2013)
Left brain tends to be used as an analytical control to most thoughts and actions. The right brain relates more to visual, imaginative, intuitive, and synthesizes all faces. Many great ideas have been created from one’s consciousness in exploring dreams through the power of imagination and exploring all possibilities to find a new life vision giving a birth of new ideas. Great ideas tend to originate from imagination power and work achievements of left and right brains. Conceptual era should be equipped with left brain reasoning by mastering six intellegences focusing on the importance of the work rights of brain to develop thought suitable to soul demands. A new vision of life is really important in the field of creative process because people with high creativity always have chances to reorient their visions. New vision is created by the power of imagination that will results in aesthetical newness. Art moves to interdisciplinary areas and continues to enrich the values promoted by art aesthetics that cannot be strictly and uniformly defined. Through an exploration of the power of imagination and sensitivity intuition, creative vision and aesthetical ideology creating new new aesthetics will continue to thrive and up to date. Keywords: new vision, right brain, imagination, new aesthetics